State-business relations and the financing of the welfare state in Argentina and Chile: Challenges and prospects - Jamee Moudud; Esteban Pérez Caldentey; Enrique Delamonica (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper examines the ways in which taxation, social and labour (T S & L) policies in Argentina and Chile have been shaped by state-business relations and capital-labour relations in a context where business organizations/associations have different degrees of cohesiveness through time. At the heart of the theoretical framework is the view that social democratic/egalitarian/progressive policy proposals must incorporate the role of unequal power relations in the shaping of such policies. The authors suggest that the implementation and maintenance over time of such policies by the state is a contested process that mediates between business pressures for pro-business policies and the larger societys demands for social justice. This suggests the need for what they call a political and policy mix (PPM) that could maintain business confidence in the presence of strong unions and a strong welfare state - at least for a while. Yet the authors suggest that designing a well-functioning PPM is hardly an easy task, given the contested and turbulent terrain in which the state operates. Finally, they argue following Schumpeter, Kaldor, and others that there is a need for a fiscal sociology of taxation in order to understand historically determined economic, social, political, and institutional factors that shape the level and composition of taxation which is central to financing of social democratic policies.
Keywords: 330